Data-Driven Decision-Making: Leveraging Analytics for Performance Improvement - S. Dhivya devi, A. Vinay Bhushan, G. Lakshmi; Usman AK, Subhajit Brojabasi, Syed Shujauddin Sameer (Journal of Informatics Education and Research, 2024)
In the modern world, businesses, societies, and investigators all depend on decisions. However, to make intelligent judgments, they must embrace emerging innovations such as big data, analytics, ML, and automatic decision-making. To improve on traditional decision theory, this article presents a new data-driven theory. It asserts that analytical tools and big data need to be viewed as individual factors, that individuals who make decisions and analytics can work together to achieve cooperative logical thinking, and that significant incorporation of data and analytics with traditional decision-making aspects may outcome in more effective, more informed decisions. The theory is expanded upon in the article, along with examples of how it is used to data-driven decisions.